Introduction. Authoritarianism, popular insurgencies, and labor movements in Latin America - Nowak, Jörg (2024)
Introduction to issue 97 of Apuntes, dedicated to the theme "Authoritarianism, Popular Insurgencies, and Labor Movements in Latin America."